PEMBANGUNAN APLIKASI INFORMASI KATERING DI KOTA PADANG BERBASIS ANDROID - Yance Sonatha; Indri Rahmayuni; Lastri Fatika Sari (Politeknik Bisnis Indonesia, 2021)
The need for food is one of the main human needs. In the era of the COVID-19 pandemic, one of the businesses that has survived is the business of providing food or culinary. With the advancement of technology, various media and methods have been successfully developed to market food products. The catering business is a business that is quite popular in the culinary field. In the city of Padang there are more than 30 catering businesses but most of them still do traditional marketing. So far, the process of searching and ordering catering in the city of Padang is still using a manual system, through advertisements in mass media and electronic media as well as through word of mouth promotion systems. This study aims to build an application that provides catering information. The research was conducted using the waterfall method which resulted in an application built with the android platform so that it can be accessed by users using smartphones. This application has succeeded in providing information about a list of menu options, prices and equipped with ordering features and location search features.